2021
DOI: 10.1007/s11605-020-04817-x
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Facility Is Associated with Higher Utilization of Esophagectomy and Improved Overall Survival for Esophageal Carcinoma

Abstract: Background Operable esophageal carcinoma is potentially curable with surgical resection. The short-term outcomes and overall survival rate for operable esophageal carcinoma may be impacted by the healthcare facility type where patients receive care. Methods A total of 37, 271 cases with the American Joint Committee on Cancer clinical stage I, II, and III esophageal carcinoma that were reported to the National Cancer Data Base at over 12,721 facilities were analyzed. Healthcare facilities were dichotomized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…For some pathologies, outcomes are reportedly better at academic versus community hospitals regardless of caseload, which may be related to more homogeneity in biological behavior of the pathology at hand. [33][34][35] However, the present study demonstrated that neither facility type nor volume predicts OS in HNMM. Relative case volume may not be significant because HNMM is such a rare disease with a very poor prognosis.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…For some pathologies, outcomes are reportedly better at academic versus community hospitals regardless of caseload, which may be related to more homogeneity in biological behavior of the pathology at hand. [33][34][35] However, the present study demonstrated that neither facility type nor volume predicts OS in HNMM. Relative case volume may not be significant because HNMM is such a rare disease with a very poor prognosis.…”
Section: Discussioncontrasting
confidence: 80%
“…However, hospital volume and academic status are not always congruent. For some pathologies, outcomes are reportedly better at academic versus community hospitals regardless of caseload, which may be related to more homogeneity in biological behavior of the pathology at hand 33‐35 …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these facilities offer greater access to experienced esophageal surgeons and advanced postoperative care, and this drives an increase in the number of esophagectomies performed. 16 Facility case volume was not an independent predictor of overall survival in our study. Although high overall case volume successfully correlated with a higher likelihood of surgery in both academic and community facilities, it was only associated with improved survival in academic facilities.…”
Section: Discussioncontrasting
confidence: 75%
“…This may be surprising, as academic centers generally show superior outcomes following esophagectomy for esophageal cancer 19 . Considerations at academic institutions that may affect LOS include increased diagnostic tests and work‐up 20 and increased disease complexity, such as advanced clinical stage 19 . Our analysis also showed that white race (versus non‐white race) was associated with a shorter LOS.…”
Section: Discussionmentioning
confidence: 73%
“…Academic institution as the hospital facility had the greatest association with increased LOS after esophagectomy for esophageal cancer. This may be surprising, as academic centers generally show superior outcomes following esophagectomy for esophageal cancer 19 . Considerations at academic institutions that may affect LOS include increased diagnostic tests and work‐up 20 and increased disease complexity, such as advanced clinical stage 19 .…”
Section: Discussionmentioning
confidence: 99%